Floristic diversity and vegetation patterns along disturbance gradient in arid coasts in southern Mediterranean: Case of the Gulf of Gabès, southern Tunisia. Issue 3 (3rd July 2018) - Neji, Mohamed; Serbaji, Mohamed Moncef; Hardy, Olivier; Chaieb, Mohamed
ABSTRACT: Knowledge about vegetation patterns along disturbance gradients is essential for conservation and management of coastal habitats in arid regions. This study focuses on the floristic diversity and the factors controlling the vegetation structure in the Gulf of Gabès (Tunisia). For this purpose, the floristic diversity of 120 relevés belonging to three coastal sites with different disturbance levels (40 relevés per site) was analyzed in relation with 10 environmental and anthropogenic factors. Therophytes constitute 54% of the 237 plants species belonging to 44 families identified in the present study. The species richness and floristic diversity indices exhibited a similar trend and peaked in the slightly disturbed site ( H ′ = 3.38; S = 176). The similarity between sites was relatively low and reached its maximum between the little and the highly disturbed sites. Two-way indicator species analysis and detrended correspondence analysis applied on the floristic data resulted in groups mainly determined by disturbance level by explicitly segregating the three sites. Canonical correspondence analysis (CCA) indicated that the spatial pattern of species composition was mainly influenced by anthropogenic variables. Partial CCA revealed that the effect of anthropogenic variables on floristic composition was thrice higher than the effect of environmental variables (57.5% vs. 18.4%, respectively). Overall, this study provides a broad understanding of the floristic diversity and vascular plant richness in the Gulf of Gabès. The obtained results reflected a disturbance–diversity pattern and thus revealed the obvious importance of maintaining the intermediate disturbance for biodiversity conservation and monitoring.